Camaraderie of writers : a quality enhancement plan (QEP) for cultivating excellence in student writing - Oxenreider, Anne Louise (2010)
This thesis presents the Quality Enhancement Plan (QEP) for the development of a writing fellows program at Montreat College, a small, Christian, liberal arts college in Western North Carolina. This expression of a Writing Across the Curriculum (WAC) program model seeks to expand the writing processes and increase the self-assessment abilities of our undergraduate students. The program adds classroom-based peer writing tutors and a focused faculty development program to our already successful drop-in writing center services. The QEP document includes a description of the development process, needs assessment process, Student Learning Objectives (SLOs), five-year budget with narrative, and the assessment plan. The introduction describes the roles of each program participant in the QEP.